PSVII-39 Improvement of trace mineral homogeneity in feed using a single-particle glycinate mineral blend. (7th December 2018) - Ionescu, C; Wall, E
Abstract: Trace mineral heterogeneity in feed and consequently in animal consumption is often a challenge in nutritional management. The objective of this study was to determine if a formulated product combining several metals into a single particle improves trace mineral homogeneity compared to a mixture of individual products. Two supplements containing Cu, Zn and Mn were created. The first was a mixture of individual metal-glycinate complexes (TradMix ). The second was a spray-granulated product, with each particle containing all 3 metal-glycinates (IFT ). The supplements were sampled (N = 10 /treatment) and their metal levels analyzed. Supplements were then incorporated into feed at 360 g/t for IFT and 400 g/t for TradMix, then randomly sampled (N = 10/treatment) for analysis of metal levels. Equality of variance was determined using the Folded F test (SAS). Mean mineral concentration ± SD in TradMix vs. IFT was 1.18 ± 1.053% vs. 1.32 ± 0.008% for Cu, 10.49 ± 0.538% vs. 12.22 ± 0.092% for Zn, and 10.98 ± 0.199% vs. 12.55 ± 0.053% for Mn, respectively. Variation in concentration of all minerals was lower in IFT ( P < 0.0001). In the feed, mineral concentration ± SD in TradMix vs. IFT was 14.86 ± 5.85 ppm vs. 15.69 ± 1.70 ppm for Cu, 71.62 ± 17.23 ppm vs. 78.5 ± 8.99 ppm for Zn, and 65.03 ± 11.39 ppm vs. 62.01 ± 7.89 ppm for Mn, respectively. The variation in Cu was reduced in IFT ( P < 0.001); for Zn it tended to be reduced ( P = 0.06) and for Mn it was not different ( P ≥ 0.20). We conclude that the use of a formulated product containing all metals in a single particle improves trace mineral homogeneity. Additional research is needed to determine the implications for decreased variation in animal trace mineral status and performance.